2018
DOI: 10.1159/000487129
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Recognition, and Treatment of Dementia in Assisted Living Facilities

Abstract: Background/Aims: Dementia and psychiatric disorders are common in assisted living facilities (ALFs) and have suboptimal rates of recognition and treatment. Therefore, we aimed to obtain a direct estimate of the prevalence of cognitive impairment and especially dementia among residents of ALFs in western Slovakia and their rates of primary recognition and adequate treatment. Methods: We conducted two cross-sectional studies. Ten ALFs within the city of Bratislava were chosen for the study in 2004, and again in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…Our results are comparable with the results from previous studies done in Australia [14], Brazil [15], Canada [16], China [17], Czech Republic [9], Denmark [8], Germany [18], Greece [19], Italy [20][21][22], Israel [23], Portugal [24], Slovakia [25] and the USA [26][27][28]. The most interesting comparison is with the Austrian [29], Italian [20][21][22] and Czech [9] studiespopulations with whom we share a similar cultural and historical background.…”
Section: Clock Drawing Testsupporting
confidence: 89%
“…Our results are comparable with the results from previous studies done in Australia [14], Brazil [15], Canada [16], China [17], Czech Republic [9], Denmark [8], Germany [18], Greece [19], Italy [20][21][22], Israel [23], Portugal [24], Slovakia [25] and the USA [26][27][28]. The most interesting comparison is with the Austrian [29], Italian [20][21][22] and Czech [9] studiespopulations with whom we share a similar cultural and historical background.…”
Section: Clock Drawing Testsupporting
confidence: 89%
“…In total, 36 studies reported data from Europe ( 20 , 22 24 , 28 , 30 , 33 , 35 , 37 , 48 , 52 , 55 58 , 60 , 63 , 65 , 73 77 , 82 , 86 88 , 90 93 , 95 , 96 , 98 , 101 , 104 ) and 22 studies reported data from Asia ( 25 , 31 , 38 , 39 , 43 , 59 , 62 , 66 , 68 – 72 , 78 81 , 83 , 85 , 89 , 94 , 99 ). Seventeen studies reported data from the USA ( 17 19 , 26 , 34 , 36 , 40 – 42 , 45 , 49 51 , 61 , 100 , 102 , 103 ).…”
Section: Resultsmentioning
confidence: 99%